2020
DOI: 10.3390/brainsci10110867
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Review of Smartphone Apps for Tinnitus Management and Treatment

Abstract: Tinnitus is a complex and heterogeneous psycho-physiological disorder responsible for causing a phantom ringing or buzzing sound albeit the absence of an external sound source. It has a direct influence on affecting the quality of life of its sufferers. Despite being around for a while, there has not been a cure for tinnitus, and the usual course of action for its treatment involves use of tinnitus retaining and sound therapy, or Cognitive Behavioral Therapy (CBT). One positive aspect about these therapies is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 68 publications
0
17
0
2
Order By: Relevance
“…Therefore, the number of tinnitus-related apps available at any time is difficult to report but recent reviews have suggested over 200 ( 116 , 118 ). However, a common observation was that very few apps had been scientifically validated or tested for efficacy, and there was a high risk of bias in many of the studies that were available ( 83 , 117 ). Furthermore, Sereda et al ( 113 ) found that most of the apps that they reviewed were self-help apps that did involve clinicians.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the number of tinnitus-related apps available at any time is difficult to report but recent reviews have suggested over 200 ( 116 , 118 ). However, a common observation was that very few apps had been scientifically validated or tested for efficacy, and there was a high risk of bias in many of the studies that were available ( 83 , 117 ). Furthermore, Sereda et al ( 113 ) found that most of the apps that they reviewed were self-help apps that did involve clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent reviews have previously identified tinnitusrelated apps, although scope, inclusion/exclusion criteria, and definitions differed between them (83,(113)(114)(115)(116)(117)(118). Tinnitus patients have been surveyed about their preferences in apps ( 113), but aside from a small trials (119) evidence of benefit from apps for tinnitus is absent.…”
Section: Appsmentioning
confidence: 99%
“…It has already been suggested that mobile applications offer a promising way for tinnitus assessment and treatment [ 76 78 ]. Hence, several specific mobile applications will be developed for the UNITI-RCT creating the opportunity to significantly reduce the number of tinnitus-related clinical visits and as such the necessary health care resources.…”
Section: Discussionmentioning
confidence: 99%
“…According to De Ridder et al ( 2021 ), “The capacity to measure the incidence, prevalence, and impact will help in identification of human, financial, and educational needs required to address acute tinnitus as a symptom but chronic tinnitus as a disorder.” Mobile health apps for tinnitus have the potential of assisting patients in self-assessment of their condition and of delivering insights on tinnitus heterogeneity to the medical experts, as reported by Probst et al ( 2017 ); Cederroth et al ( 2019 ), and Pryss et al ( 2019 , 2021 ) among others. This is particularly the case for mHealth apps that collect Ecological Momentary Assessments (EMA): several studies on mHealth tinnitus apps have demonstrated that EMA recordings deliver insights on tinnitus stages during the day and on the interplay of personal traits and severity of tinnitus symptoms (see, e.g., Probst et al, 2017 ; Mehdi et al, 2020 ; Unnikrishnan et al, 2020a ; Jamaludeen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%